IN VITRO ANTHELMINTIC AND ANTI-AMYLASE PROPERTIES OF GARCINIA PEDUNCULATA ROXB. ETHANOLIC EXTRACT - Sarmah, Pinky; Kobing, Nako; Gogoi, Jyotchna; Dutta, Ananta Madhab (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: The present study aims to investigate in vitro anthelmintic and anti-amylase properties of the ethanolic fruit extract of Garcinia pedunculata. Methods: For the study, mature fruits of G. pedunculata were collected from local markets during April-May. Fleshy pericarps of fruits were chopped into small pieces, dried and extracted by using a Soxhlet apparatus. Ethanol extract of G. pedunculata was used for evaluation of in vitro anthelmintic and anti-amylase activities. In vitro anthelmintic activity was evaluated in animal models, Pheretima posthuma, an earthworm species. In vitro anti-amylase activity was evaluated by using zymographic, achromic point analysis (Starch-Iodine method) and spectrophotometric method [Di Nitro Salicylic acid (DNS)–Maltose method]. Results: Ethanolic extract of G. pedunculata showed anthelmintic activity at a concentration of 75 mg/ml, paralysis and death timing was reported at 0.62±0.26 min and 1.42±0.07 min, respectively. The reference standard (Albendazole) showed paralysis time: 2.13±0.28 min and death time: 5.12±0.29 min. In the anti-amylase study, a zymographic density analysis of G. pedunculata showed significant variation in band intensity as compared to Starch–Iodine achromic point analysis and DNS–Maltose method. A concentration of 1.5 mg/ml of extract showed inhibition of amylase: 67.65±1.53 % as compared to other concentrations and control sets. Conclusion: It could be concluded that ethanolic extract of G. pedunculatahas biological properties which could be utilised in medicine by characterising its bioactive components.